Pharmacokinetics of active compounds of a Terminalia chebula Retz. Ethanolic extract after oral administration rats using UPLC-MS/MS - Yao, Guangzhe; Miao, Xinxin; Wu, Mengxuan; Lv, Zhenguo; Bai, Yu; Chang, Yanxu; Ouyang, Huizi; He, Jun (Frontiers in Pharmacology, 2023)
Terminalia chebula Retz. (TC) is a well-known herbal medicine and rich in chemical components with multiple pharmacological effects. In this study, an ultra-performance liquid chromatography-tandem mass spectroscopy (UPLC-MS/MS) method was developed and used to detect the blood concentration of nine active compounds (chebulic acid, gallic acid, protocatechuic acid, corilagin, chebulagic acid, chebulinic acid, 1,2,3,4,6-O-pentagalloylglucose, ellagic acid and ethyl gallate) in rat after oral administration of TC extracts. Protein precipitate with methanol was used to pretreat the plasma samples, and caffeic acid were used as the internal standards (IS). The intra- and inter-day precisions of the compounds were less than 14.6% and the accuracy ranged from -11.7% to 13.5%. The extraction recoveries of the compounds were in the range of 88.0% to 108.4% and the matrix effect ranged from 86.4% to 115.9%. According to the results of stability test, nine analytes were stable under four storage conditions with relative standard deviations less than 13.7%. The validated UPLC-MS/MS method was successfully applied for the plasma pharmacokinetics analysis of the TC extracts, and the pharmacokinetic results showed that among the nine components, the area under the concentration-time curve (AUC(0-tn), 231112.38±64555.20 h ng/mL) and maximum concentration (Cmax, 4983.57±1721.53 ng/mL) of chebulagic acid were relatively large, which indicated that it had a higher level of plasma exposure. The half-life of elimination (T1/2) of chebulinic acid, corilagin and chebulagic acid were 43.30, 26.39 and 19.98 h, respectively, suggesting that these analytes showed prolonged retention and metabolize more slowly in vivo. This study would provide a theoretical basis for the further clinical application of TC.